(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2013)
Integrated Architecture Monograph by WuÂ Liangyong Foreword by Lucio Valerio Barbera Translations by Anna Irene Del Monaco, Liu Jian, Ying Jin, George Michael Riddel, Roberta Tontini Afterword by Anna Irene Del Monaco Â Integrated Architecture is both a historical and contemporary work. The book was first published in 1989 by Wu Liangyong, one of contemporary Chinaâ€™s most influential architects and theoreticians with the title A General Theory on Architecture. His eminence is also recognised by the international architectural community, above all, the group of architectural and urban planning theoreticians battling for a more decisive reform to the concepts, methodologies and practices presiding over the construction and requalification of the contemporary metropolis. I first met professor Wu Liangyong in 2005 at the Faculty of Architecture at the Tsinghua University of Beijing; his Faculty. Wu Liangyong founded the school in 1949 â€“ at the age of 24 â€“ together with Liang Sicheng, the father of modern Chinese architectural studies. From this moment â€“ more than sixty-seven years ago â€“ professor Liangyong has remained a central figure in Beijingâ€™s academic community. He remains a constant source of inspiration, not only national, to education reforms and, above all, theoretical, methodological and operative research into architecture, the city and the territory. He is a rare figure, present throughout a lengthy historical period witness the world over to tumultuous upheavals in society and its cities. A period whose most dramatic and exalting manifestations were perhaps to be found in China; a period of war, of hope, of revolutions, of great leaps forward, of presumptions, horrors, errors, new leaps forward and incomprehensible economic growth; of irreversible social and cultural metamorphoses and â€“ what interests us most as architects â€“ of staggering urban growth and territorial transformations. The intellect of this minute and genteel figure held fast against the storms of history. The observation of events and the humanist and scientific principles of his personal culture continuously nourished an increasingly more effective reflection on the meaning of architecture in todayâ€™s world. He also clearly saw its inextricable ties to the substance of the city and the impossibility to substitute the figure of the architect â€“ scientist, humanist and artist. A few years after our meeting, having absorbed direct lessons from Wuâ€™s work as an architect and theoretician, I proposed an Italian translation of an anthology of his writings. The material was to be drawn from his many books and essays on architecture and the city published continuously over the course of his incomparable career. Professor Wu Liangyong responded with a challenge: in lieu of this anthology of texts he proposed a full translation, in Italian and English, of a book published twenty years ago: 1989â€™s A General Theory on Architecture. Given the pace of cultural debate it would not have been out of place to imagine a book firmly sedimented in history. I understood, instead, that it was a milestone in the expression of Wu Liangyongâ€™s ideas; a benchmark that, in all likelihood, served as the starting point for his later theories, even the most recent. Published in other fundamental essays, they range across the vast field of human settlements, touching on all components of the man-made environment (Lucio Valerio Barbera).